Efeito da substituição de sacarose por edulcorantes naturais em sorvete de iogurte adicionado de jambolão (Syzygium cumini) - Abreu, Thaianaly Leite (2019)
Yogurt ice cream, frozen yogurt, is an innovative product that is lower in calories than regular ice cream. It is an edible ice cream that has become popular among adults due to its potential to exert beneficial health effects. Furthermore, when ingredients with bioactive compounds, such as jambolan, are added to this product, it can promote several health benefits to the consumer. The jambolan (Syzygium cumini) is a fruit rich in phenolic compounds, such as anthocyanins, quercetin, ellagic acid, and other components that have proven antioxidant power, but there is little incentive and techniques to use this fruit in the regional production chain, so exploring this potential becomes a good alternative. The demand for products with reduced sugar content is not only due to the consumer interest in products related to weight control diets but also the growing concern with the benefits brought by them to health. Therefore, this study aimed to evaluate the quality parameters of yogurt ice cream with jambolan pulp, prepared with partial and total replacement of sucrose by natural sweeteners (xylitol and agave syrup), regarding sensory, physicochemical, bioactive, and microbiological characteristics. Three formulations of yogurt ice cream were prepared (SC, S1, and S2) that differed in the amount of pulp, sucrose and sweeteners. Given the assay of antioxidant activity and bioactive compounds presented by the present research, it is suggested that jambolan is an excellent source of phenolic compounds that present antioxidant activity. The production of the proposed yogurt ice cream is technologically feasible since it worked as a vehicle of the bioactive compounds present in jambolão, the partial replacement of sucrose, which did not significantly modify the physicochemical, bioactive, and sensory characteristics. In addition, the jambolan yogurt ice cream represents a new product intended for the expanding market, aimed at a public interested in healthy eating habits.